Protection of the Rights of Children and Women in Islamic Family Law: A Study of Hadhanah, Guardianship, and Marriage Breakdown in the Perspective of Fiqh and a Compilation of Islamic Law in Indonesia - Hanifah Muslimah; Fatiha Nur Laili Azizah; zahra rohmatic; Aulia Azizah P Pure; M Adil Hakim Al Hadi (PT. Nawa Edukasi Nusantara, 2026)
The protection of children's and women's rights is a central issue in Islamic family law and remains highly relevant in the contemporary Indonesian context. This article aims to analyze the protection of children's and women's rights through three main instruments, namely child custody (hadhanah), guardianship (wilayah), and marriage dissolution regulations. This study employs a normative juridical method using statutory and conceptual approaches by examining the Qur’an, Hadith, classical fiqh literature, and the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI) as the applicable legal framework in Indonesia. The discussion shows that hadhanah represents a parental responsibility that continues after divorce based on the best interests of the child. Guardianship serves as a legal protection mechanism for minors in personal, property, and marital matters. Meanwhile, marriage dissolution regulations under the KHI combine Islamic legal principles with modern legal certainty to protect women and children from its legal consequences. These instruments collectively reflect the objectives of maqashid al-shariah, particularly hifzh al-nasl and hifzh al-nafs, in Indonesian Islamic family law.